Distribution of non-native invasive species and soil properties in proximity to paved roads and unpaved roads in a quartzitic mountainous grassland of southeastern Brazil (rupestrian fields) - Barbosa, Newton P. U.; Wilson Fernandes, G.; Carneiro, Marco A. A.; Júnior, Lélis A. C. (Biological invasions, 2010)
One of the most important disturbances of roads is the facilitation of the increase of non-native invasive species into adjacent plant communities. The rupestrian fields of Serra do Cipó , a montane grassland ecosystem in southeastern Brazil, are recognized for their enormous richness of species and endemism rates. The presence of non-native invasive species in this ecosystem could threaten the existence of the native flora and its associated organisms. The aim of this study is to understand how non-native invasive species and native species are distributed along paved and unpaved roads, in a montaneous grassland ecosystem such as the Brazilian rupestrian fields. The two road surfaces provide differing gradients from their edges with respect to nutrients, soil chemical aspects and plant species diversity. High content of calcium at the roadside in the paved road resulted from the paving process, in which limestone gravel is used in one of the several paving phases. In these newly created habitats the toxicity of aluminum is drastically reduced and nutrient enriched, hence representing favorable sites from where non-native invasive species are capable to colonize and grow for undetermined period waiting the chance to invade the adjacent pristine habitats. Disturbances provoked by any natural or human-caused event can provide the opportunity for the non-native invasive species to colonize new plant communities.